Mass media and aspiration achievement of children on primary education - Gunartati Gunartati; Siti Eshah Mokshein (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
Child labor is the social phenomena that not only exist in Indonesia but also in other developing countries. These children work in several sectors including in the small industrial sector. As a young generation, they also must be able to compete in the work world. Therefore, aspiration achievement is an urgent matter and must be considered by stakeholder. On the other hand, the influence of globalization is increasingly global, especially in the field of communication. Representations from this field include on the mass media. Child labor who lives in the global era is also very familiar with the mass media. The study aimed to reveal the influence of information on radio, television and family environment on aspirations achievement of child labor at the leather industry handicraft center in Wukirsari, Imogiri, Bantul. The population of this study was child workers aged 10-14 years, who worked in the leather industry handicraft centers in Wukirsari, Imogiri, Bantul and were still taking study in school, which had a total of 119 child workers. Questionnaire instruments used to obtain data of all variable. The regression analysis technique used to test the hypothesis. The results of the study showed that there was a significant positive influence on the habit to follow information from the mass media and the family environment on the aspirations of child laborers at the leather industry handicraft center in Wukirsari.